The Development of Professional Competency Certification Assessment Model for Junior Mobile Programmers - Novaliendry, Dony; Ahyanuardi; Irma Yulia Basri; Noper Ardi; Nathasyah Utami Hakim; Muhammad Fadilh Putra Pratama; Nenny Mahyudin, (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Indonesia’s Vision 2045 is an essential basis to determine the direction of the country’s development in line with four main pillars which include the development of human resources (HR). This involves producing quality, healthy, intelligent, adaptive, innovative, and skilled human resources with character. The achievement of this goal requires the improvement of the competence and professional certification quality towards ensuring HR are reliable and competent in different fields such as the vocational area which involves Informatics Engineering (IT). Therefore, this research was conducted based on the gap observed in HR which is indicated by a lower proportion of Indonesian workers in the IT field compared to other ASEAN countries. It was also observed that the assessment process and results of the Junior Mobile programmer scheme by the Professional Certification Institute (LSP) for Digital Technology have not been optimally tested. This is indicated by the fact that the assessment activities are being conducted without the full implementation of a centralized and systematic technology-based system, thereby causing problems in the remote assessment process. Moreover, professional associations, academia, and industry were not involved in designing a tested and reliable assessment model. I this research was conducted from March 2022 to December 2023 with the trial subjects from the Digital Talent Scholarship (DTS) training program, Vocational School Graduate Academy (VSGA) of the Ministry of Communications and Informatics. There were 40 sessions which consist of 20 for the experimental class and 20 for the control class. Furthermore, the data collection instruments included questionnaires, documentation, interview guides, observations, and competency tests while descriptive and quantitative analyses were conducted through the I'ken V and factor analysis tests using the LISREL and SPSS applications.